A Note on Directional Wavelet Transform: Distributional Boundary Values and Analytic Wavefront Sets - Felipe A. Apolonio; Daniel H. T. Franco; Fábio N. Fagundes (International Journal of Mathematics and Mathematical Sciences)
By using a particular class of directional wavelets (namely, the conical wavelets, which are wavelets strictly supported in a proper convex cone in the k-space of frequencies), in this paper, it is shown that a tempered distribution is obtained as a finite sum of boundary values of analytic functions arising from the complexification of the translational parameter of the wavelet transform. Moreover, we show that for a given distribution f∈𝒮′(ℝn), the continuous wavelet transform of f with respect to a conical wavelet is defined in such a way that the directional wavelet transform of f yields a function on phase space whose high-frequency singularities are precisely the elements in the analytic wavefront set of f.